Development of single seedling nursery tray for the System of Rice Intensification - Zubairu, Usman Bashar (2013)
One of the main problems in the adaption of the System of Rice Intensification (SRI) techniques is high labor requirements for manual planting of the single seedling in the field. Seedling quality and transplanting skills play a vital role in promoting optimum yield. However, the existing seedling raising methods remain a challenging constraint among SRI practitioners due to the absence of a mechanized adaptation of SRI planting and spacing standards. Ironically, farmers are forced to pay for replanting hence increasing the production cost. Therefore, this study was intended to create modern techniques for increasing the quality and transplanting potentials of rice seedling by improving SRI nursery and reducing seedlings transplanting shock. Prior to designing of SRI nursery tray, a study was conducted on the physical properties of MR219 rice seed to determine the basic parameters of the seed. These properties were evaluated as a function of moisture content at 14.3, 18.9 and 22.5% dry basis. The results revealed that length, width and thickness increased with increasing moisture content from 9.6 to 10.2, 2.2 to 2.3 and 1.9 to 2.0 mm, respectively. Similarly, M1000 increased from 27.1 to 29.9g as well as arithmetic and geometric mean diameters from 4.8 to 4.9 and 3.4 to 5.7 mm. Bulk density, sphericity, and surface area increased with moisture content from 517.7 to 543.5 kg/m3 , 0.358 to 0.362% and 37.2 to 42.6 mm 2 respectively. A decrease was observed for true density (1244.6 to 1197.5 kg/m3 ) and porosity (58.4 to 54.6) as seeds rewetting increased. These technical information were used in SRI tray design and development. The single seedling nursery tray of rectangular shape was developed with length 635 mm, width 335 mm and height 40 mm with open top and square growing cavities of 15 x 15 mm separated by a thickness of 1mm with 30 mm height. A sliding base plate 635mm long, 332 mm wide and 4mm thick, served as a valve in holding and placing seedling for transplanting into the field. The tray was capable of producing 924 vigorous and viable independently separated seedlings for transplanting singly upon SRI spacing standard. Seed selection was conducted before sowing as every seed matters when using the SRI tray. The experiment revealed that 100% germination after ten days was obtained from the sunken MR219 seeds collected in 80 g/L of NaCl solution. These values reported a decrease in germination (85%) with increasing NaCl concentration (120 g/L), with least germination vigor of 62% in water 3 days after sowing. A 100% seed sprouting was also recorded from the selected seeds when primed for six hours. A SRI seed picker was also developed to place the sprouted seeds in SRI tray. It was made with 924 cone shape seed pickers for attachment of individual seeds and dropping the seeds into 924 SRI tray holes. The fastest picking and dropping level was reported at 150 g/L of tapioca and water solution. Three different media, namely Soil + Burnt husk (1:1) as M1, Soil + Compost (1:1) as M2 and compost alone as M3 were used to evaluate the growth performances after ten (10) days. The measured parameters were seedling height (SH), leaf length (LL), leaf number (LN), root length (RL) and loosening index (LI) from the SRI tray and compared with seedlings from the conventional tray. The SAS and Duncan’s mean results revealed that M2 had the highest significant values for SH, LL and LI with the mean values of 15.56 cm, 10.93 cm and 75 seconds but reported a decrease on RL (8.93 cm) when compared with M1 and M3 having RL values of 9.23 and 10.27cm, respectively. Likewise, M1 indicated a drop on SH with mean value of 14.53cm and also LL with the mean value of 10.03 cm but reported a mean value of 9.23 cm on RL after M3.